Singapore in Efforts to Increase the Air Pollution Index - Rahmawati Hasyim, Austiva Alma; Winarko, Juli; Hanindya, Marcellina Mutiara Firsty (Journal of ASEAN Dynamics and Beyond, 2020)
According to the theory of environmentalism, human civilization has a negative impact on the environment because of industrialization. It means that it cannot be separated from the perspective of the green movement that underlies environmentalism. Environmental issues are an implicative issue because it creates a chain reaction for many parties. In general, cities in the Southeast Asia region are facing the same issue, such as air pollution obtained from factories and motorized vehicles. Within the regional scope, ASEAN has taken the initiative to create regional cooperation that specifically addresses cross-border haze and other environmental issues within the framework of ASEAN cooperation. One of the ASEAN member countries, Singapore was able to hold down the Air Pollution Standard Index and become the 5th ranked country in Asia Pacific with the best air quality. Thus, Singapore experience better air quality than most other countries in Southeast Asia. The achievement of Singapore also involves government policies that pay great attention to environmental issues. The results of this paper provide views and alternatives that can be applied by other countries' governments, related to environmental issues